Preschool and School-aged Children’s Problematic Internet Use: The Role of Parental Involvement, Parental Attitude on the Internet Use and Children’s Activities Online - Puchalska, Valerija; Jusienė, Roma; Breidokienė, Rima (Psichologija, 2023)
The use of the Internet for communication, education, and entertainment has become an important part of the lives of all users, including teenagers and children. The role of parents is considered to be important to ensure children’s safe use of the Internet and to protect them from excessive involvement in online activities. The current study aimed to investigate the associations between problematic Internet use in children aged 6–14 years and their parents’ involvement in their children’s Internet use and parents’ attitudes towards their child’s Internet use. The sample consisted of 719 parents with children aged six to fourteen years (mean age 9.04 years, 55.2% of the sample were boys). Parents completed the Compulsive Internet Use Scale (Meerkerk et al., 2009) to assess their children’s problematic Internet use, and answered questions about their attitudes towards the impact of the Internet on their child’s health and relationships, their involvement in their child’s Internet use, their child’s online activities, and the time spent using screens. The data were collected as part of the research project „Long-term effects of screens on children’s physical and mental health“, in spring 2021. The results showed that children’s problematic Internet use (PIU) is related to children’s age, the total duration of screen use, online activities, and parents’ attitudes on the impact of the Internet on children’s health and relationships. In a sample of children aged 6–10 years, greater PIU was predicted by male gender, longer screen time, greater children’s involvement in online entertainment and social activities, and less favorable parental attitudes toward children’s health and relationships. Similarly, the same variables predicted PIU in 11–14-year-olds, except for social activities online. The relationships between the variables were also analyzed using structural equation modeling: models add to the results by indicating indirect associations between parental attitudes towards the Internet and children’s PIU in both age groups. In contrast, it is only in younger children that parental involvement indirectly predicts PIN.